Use and interest in social networks among older people from a gender perspective. A study in the andalusian senior people universities - Julio Barroso Osuna (Tecnología, Ciencia y Educación, 2017)
The data provided in this article arise from an investigation carried out as a regional level in the different andalusian senior people universities. One of the purposes of this study is to know the situation of senior people in social networks according to gender. A total of 294 students belonging from provincial programs of the different andalusian senior people universities participated. A questionnaire was elaborated, after a review of the literature and taking as a reference researches carried out about the subject of the study. The results indicate that the gender gap between the collective has practically disappeared as in the younger generation. Likewise, both genders express the same concerns as being part of social networks, benefits of use, reasons why they decided to be part of them or tools used to join. There are significant differences about interest, purpose, frequency of use and connection devices used between men and women.